2017
DOI: 10.1016/j.ultrasmedbio.2017.08.965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Hypoxic Microenvironment after Radiofrequency Ablation on Residual Hepatocellular Cell Migration and Invasion

Abstract: Clinical observations have shown that the boundary of tumor ablation is often less than safe border and that the use of radiofrequency ablation (RFA) in the treatment of hepatocellular carcinoma (HCC) may probably accelerate its recurrence and metastasis. RFA can cause the formation of a transition zone between normal liver tissues and necrotic coagulation, where blood stagnation and thrombosis expose residual cancer cells to a hypoxic microenvironment. As the blocked vessels are slowly reperfused, the oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It has been shown that hypoxia may facilitate the metastasis of liver cancer cells [20]. CoCl 2 treatment significantly elevated the numbers of migrated and invaded SMMC-7721, Huh7, and HepG2 cells (Figures 1(c)–1(f)).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been shown that hypoxia may facilitate the metastasis of liver cancer cells [20]. CoCl 2 treatment significantly elevated the numbers of migrated and invaded SMMC-7721, Huh7, and HepG2 cells (Figures 1(c)–1(f)).…”
Section: Resultsmentioning
confidence: 88%
“…Liver cancer is a typical malignant tumor with rich blood supply. However, many treatment methods for liver cancer usually induce a hypoxia microenvironment, including TACE and radiofrequency ablation [20, 31], and thereafter promote tumor angiogenesis and metastasis, in part related to the accumulation of HIF-1 α [32]. Overexpression of HIF-1 α promotes the growth, migration, and invasion of liver cancer cells and induces the upregulation of VEGF, which is one of the most potent angiogenic factors presented in various human cancers [33].…”
Section: Discussionmentioning
confidence: 99%
“…A lot of research has shown that the hypoxic tumor microenvironment could cooperate to regulate malignant biological functions of tumor stromal cells and cancer cells. 5,6 Increasing evidence shows that almost all primary NPC tissues contain hypoxic regions which contribute to more and more distant metastases. 29 Adipocytes used to be considered to be one of the major sources for inflammatory cytokines such as IL-6 and several complement factors.…”
Section: Discussionmentioning
confidence: 99%
“…One critically essential, yet frequently ignored, part of cancer progression is the hypoxic microenvironment, 5 which includes tumor cells and stromal cells. Adipocytes are abundant cancer stromal cells 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive outgrowth of residual hepatic micro-metastasis had been seen in the surrounding tissue of patients undergoing RFA of HCC (127). A hypoxic microenvironment that occurs in HCC post RFA has been shown to enhance the invasive, chemo-resistant and metastatic abilities of the tumour cells, these changes had been seen in patients that underwent incomplete ablation (128). Perhaps in contrast to lung cancer, a chronic inflammatory state in HCC patients may favour a tumour microenvironment that would enhance tumour growth, as suggested by the Th2 cell dominance pre and post RFA in hepatocellular carcinoma in patients with hepatitis C (129).…”
Section: Could Ablation Be Harmful?mentioning
confidence: 99%